Improving students’ arguments through collaborative learning - Shinta, Dona Kumala; Filia, F. (Indonesian Journal of Applied Linguistics, 2020)
The ability to produce argumentation is crucial for university students’ academic achievement and upcoming careers. Developing and organizing ideas to create an argument, requires students’ thinking skills. Attempts to improve students’ written arguments through collaborative learning have been conducted in numerous studies. However, there are few studies on improving students’ spoken arguments through collaborative learning, especially in Bahasa Indonesia.  Therefore, this research aims to investigate how students’ arguments improve through collaborative learning. This research uses a one group pre-test post-test design method. The participants were 21 undergraduate students from a university in Indonesia. Students were presented a video of Indonesia’s 2019 presidential debate and an argumentation model as the stimulus. Students’ arguments were recorded, transcribed, translated and analyzed to detect any improvements from the pre-test compared to the post-test. Findings show that through collaborative learning students can produce more argument component parts leading to a higher level of argument. They are also able to use their thinking skills of remember, understand, apply and analyze in the learning process. As conclusion, collaborative learning can be considered as a classroom strategy in improving students’ arguments, from producing claim, data and warrant in arguments to improving awareness in applying other component parts of backing, rebuttal and qualifier. However, there are no detections of a new component part found in students’ argument or an implementation of the highest order thinking skills, that is create.